Interpretation as a Communicative Event: A Look through Hymes' Lenses - Angelelli, Claudia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2000)
AbstractIn the last ten years, more researchers and practitioners have turned their attention to community interpreting. Issues of similarities and differences with other forms of interpreting, as well as recognition and prestige, have arisen. It is often the case that the standards of conference interpreting are blindly transferred to other forms of interpreting both for measurement and educational purposes. This blind transfer does not allow a full understanding of the complexities involved in community interpreting. Hymes' taxonomy of speaking is used to compare and analyze two interpreting events, one occurring in a community setting and the other in a conference one. The analysis suggests that there are more differences than similarities between the two settings. The differences point to a complex form of social interaction which needs attention in its own right.